Stepwise Development of an in vitro Continuous Fermentation Model for the Murine Caecal Microbiota - Poeker, Sophie A.; Lacroix, Christophe; de Wouters, Tomas; Spalinger, Marianne R.; Scharl, Michael; Geirnaert, Annelies (Frontiers in Microbiology, 2019)
Murine models are valuable tools to study the role of gut microbiota in health or disease. However, murine and human microbiota differ in species composition, so further investigation of the murine gut microbiota is important to gain a better mechanistic understanding. Continuous in vitro fermentation models are powerful tools to investigate microbe-microbe interactions while circumventing animal testing and host confounding factors, but are lacking for murine gut microbiota. We therefore developed a novel continuous fermentation model based on the PolyFermS platform adapted to the murine caecum and inoculated with immobilized caecal microbiota. We followed a stepwise model development approach by adjusting parameters (pH, retention time, growth medium) to reach fermentation metabolite profiles and marker bacterial levels similar to the inoculum. The final model had a stable and inoculum-alike fermentation profile during continuous operation. A lower pH during startup and continuous operation stimulated bacterial fermentation (115 mM short-chain fatty acids at pH 7 to 159 mM at pH 6.5). Adjustments to nutritive medium, a decreased pH and increased retention time helped control the in vitro Enterobacteriaceae levels, which often bloom in fermentation models, to 6.6 log gene copies/mL in final model. In parallel, the Lactobacillus, Lachnospiraceae, and Ruminococcaceae levels were better maintained in vitro with concentrations of 8.5 log gene copies/mL, 8.8 log gene copies/mL and 7.5 log gene copies/mL, respectively, in the final model. An independent repetition with final model parameters showed reproducible results in maintaining the inoculum fermentation metabolite profile and its marker bacterial levels. Microbiota community analysis of the final model showed a decreased bacterial diversity and compositional differences compared to caecal inoculum microbiota. Most of the caecal bacterial families were represented in vitro, but taxa of the Muribaculaceae family were not maintained. Functional metagenomics prediction showed conserved metabolic and functional KEGG pathways between in vitro and caecal inoculum microbiota. To conclude, we showed that a rational and stepwise approach allowed us to model in vitro the murine caecal microbiota and functions. Our model is a first step to develop murine microbiota model systems and offers the potential to study microbiota functionality and structure ex vivo.